Propuesta de Regeneración urbano-arquitectónica para la creación de un circuito comercial, turístico y productivo en la Zona Urbana Central del Cantón Cevallos, Provincia de Tungurahua - Solís Pazmiño, Brayan Stalin (2021)
This work contains a general overview of the current situation of the Cevallos City, and an analysis focused on its three main axes: production, commerce and tourism, and based on the diagnosis of its specific and common problems, and the analysis and conclusions of the results obtained through scientific research, proposes an urban-architectural regeneration project for the creation of a central circuit, which by the regeneration of the existing spaces and physical facilities and by new their proposals, allow the creation of new urban systems for the performance of their activities and functions in an optimal way, and that, as socializing elements, develop and assign new general and specific functions to their local and external actors, and invite them to appropriate the new public space created, to know and understand the activities and particular objectives of each one and to feel them as their own, thus creating the nexus, and the point of starting to evolve towards a common goal, minimizing the problems generated by the lack of self-identity, and consequently propitiating the appropriate conditions for the Integral Local Development without forgetting the social conscience, the strengthening and the diffusion of ancestral culture and traditions, the conservation of natural resources, and the recovery and preservation of the environment for future generations.